Epidemiological aspects of brucellosis in humans in the Health Areas of Aguas Zarcas and Los Chiles, Costa Rica, 2015-2017 - Rosales Galeano, Claudia (2020)
Brucellosis is a zoonotic disease caused by species of genus Brucella spp., with low notification and underreporting in Costa Rica, especially in humans and bovines. The seroprevalence of brucellosis and associated risk factors were determined in people who live or work in dairy farms that tested positive to bovine brucellosis in the Health Areas of Aguas Zarcas and Los Chiles, Alajuela, between 2015 and 2017, using an analytical cross-sectional study. Blood samples were collected from the subjects studied, and a survey was applied upon their informed consent. Samples were analyzed in parallel using the Rose Bengal and serum agglutination test (SAT). Descriptive statistics were conducted with the personal, cultural, and environmental factors associated with the risk for brucellosis. In addition, to determine factors associated with their serological status, odds ratios were estimated using unconditional logistic regression. Seroprevalence for smooth Brucella spp. was 12.5%. The preparation of food with unpasteurized milk products (OR = 11.0, 95% CI: 3.0-39.9), artificial insemination without adequate protection (OR = 8.84, 95% CI: 1.8-43.5), calving without basic protection (OR = 3.9, 95% CI: 1.1-14.1), and the consumption of homemade ice cream made with unpasteurized milk (OR = 7.9, 95% CI: 2.7-22.6) represented the main risk factors. Other factors showed a tendency to risk; however, the low amount of samples may have affected the statistical power of the estimates. An important exposure to smooth Brucella spp. is detected in the people that work and live on cattle farms with animals that tested positive to Brucella abortus, due to the execution of risky cultural practices. The quantitative difference between the cases reported to the epidemiological surveillance system of the Ministry of Health and the results of this study indicate that this disease should be included as a differential diagnosis for cases of acute febrile illness, and that an effective and efficient epidemiological surveillance system should be implemented.